PENERAPAN METODE STAR UNTUK MENINGKATKAN PEMAHAMAN RESIKO PESISIR PERNIKAHAN DINI MENUJU REMAJA PESISIR CERDAS DAN SEHAT DI KARIMUNJAWA - Silviana, Nining; Naili Faizatul Muna; Hamidaturrohmah; Muhammad Java Bagaskara; Mohammad Nur Arif; Ahmad Anang Adi Prayoga (PT. Karya Inovatif Nusantara, 2024)
Child marriage is a serious issue in various regions including Karimunjawa Jepara. So that it requires attention from various parties in order to minimize and reduce the number of child marriages. One of them is by providing education to Karimunjawa teenagers so that they have a full understanding of the factors and impacts of child marriage. Given that many coastal adolescents still marry at the age of 19 years and under. The method of implementation in this service activity includes several stages with the term STAR, namely socialization of child marriage prevention, training related to education on the impact of child marriage, action in the form of future mapping assistance, and reflection. The results of PKM activities show that 95% of partners understand the material on preventing child marriage. 85% of partners understand material related to ideal marriage. And 85% of partners understand the importance of reaching the minimum age in the implementation of marriage. This service activity is expected to be useful and contribute to preventing child marriage for coastal adolescents in Karimunjawa